Development of Richpeace Software-Based e-Modules on Digital Clothing Pattern Making Competence - Herdiningrum, Rinda Resi; Wahyuningsih, Sri Endah; Supraptono, Eko (Journal of Vocational and Career Education, 2021)
Mastery of computer aided design (CAD)-based design software to make fashion patterns for vocational students is very necessary, so that there is a conformity of competencies required by industry. One of the characteristics of 21st century learning is the integration of information and communication technology (ICT) in learning. Specifically, this research aims to: 1) develop richpeace software-based e-module; 2) analyze the feasibility of richpeace software-based e-module; and 3) analyze the effectiveness of richpeace software-based e-module to improve the competence of making digital fashion patterns for vocational students in the fashion study program. The research method used is Research and Development (RD). The feasibility and practicality validation analysis used the intraclass correlation Coefficients method with the help of SPSS v.19 software, while the analysis of the effectiveness of the developed e-module used the t test. Based on the results of data development and analysis, the resulting richpeace software-based emodule was declared very feasible by material experts with a score of (97.0) and very feasible by media experts with a score of (96.3). The practicality of the developed e-module was also tested by the fashion teacher, with very practical results (97.5). The e-module that was developed was also tested for effectiveness by using the t-test, with the result that there was a significant difference before and after using the e-module, with an increased value of 18.5 and a p-value of 0.000), and had an N-Gain value of 0, 93 which means that the developed e-module is very effective. Based on the results of the study, it can be concluded that the developed e-module is very feasible, very practical and very effective to improve the competence of making digital clothing patterns for vocational students in the fashion study program.